Capim-colonião e seus efeitos sobre o crescimento inicial de clones de eucalyptus × urograndis - da Cruz, Michelle Barbeiro; Alves, Pedro Luís da Costa Aguiar [UNESP]; Karam, Décio; Ferraudo, Antônio Sérgio [UNESP] (My University, 2010)
This study aimed to evaluate the guinea grass effect (Panicum maximum) on the initial growth of different Eucalyptus × urograndis clones. Two assays were established with eucalyptus clones and guinea grass seedlings. The plants were grown in plots with cement borders filled with soil. Each plot received a eucalyptus seedling. The first assay had a completely randomized experimental design, with three replications, and treatments in a 5x2 factorial scheme (five eucalyptus clones and the absence or presence of two guinea grass plants at 10 cm distance from eucalyptus seedling). The second assay was similar to the first, however with three eucalyptus clones. The experimental design was completely randomized, with five replications, and a 3x2 factorial scheme (three eucalyptus clones and the absence or presence of two guinea grass plants). The presence of eucalyptus clones did not affect guinea grass development. The eucalyptus clones that coexisted with guinea grass plants did not show differences in their development, making the clones equal when under competition. The most susceptible characteristics of eucalyptus clones to guinea grass were foliar area, shoot and stem dry matter. Clone 3 showed the most sensitivity to guinea grass, and clone 1 was the most tolerant, but all clones studied suffered a negative interference from guinea grass.
Guinea grass and its effects on the initial growth of eucalyptus × urograndis clones
Keywords: Competition; Eucalyptus × urograndis; Interference; Panicum maximum; Eucalyptus